CD44-targeted hyaluronic acid-curcumin prodrug protects renal tubular epithelial cell survival from oxidative stress damage. (1st August 2018) - Hu, Jing-Bo; Li, Shu-Juan; Kang, Xu-Qi; Qi, Jing; Wu, Jia-Hui; Wang, Xiao-Juan; Xu, Xiao-Ling; Ying, Xiao-Ying; Jiang, Sai-Ping; You, Jian; Du, Yong-Zhong
Graphical abstract: Highlights: Acute kidney injury is characterized by serious damage of renal tubules and treatment starting from the pathogenesis of the disease is necessary. Based on the overexpression of CD44 receptors on tubule epithelial cells, HA-CUR prodrug was developed to relieve oxidative stress damages. HA-CUR prodrug could be specifically internalized by epithelial cells and then achieved the increased accumulation in renal tissues. This study demonstrated the significant potential of hyaluronic acid-curcumin prodrug for ischemia/reperfusion-induced acute kidney injury and formed a basis for further development of hyaluronic acid combined with anti-inflammatory or antioxidant agents for the treatment of renal diseases. Abstract: Based on the abnormally increased expression of CD44 receptors on renal tubule epithelial cells during ischemia/reperfusion-induced acute kidney injury (AKI), we developed a hyaluronic acid-curcumin (HA-CUR) polymeric prodrug targeting to epithelial cells and then relieving oxidative stress damages. The water solubility of HA-CUR was significantly enhanced and approximately 27-fold higher than that of CUR. Cellular uptake test showed HA-CUR was preferably internalized by H2 O2 -pretreated tubular epithelial (HK-2) cells compared with free CUR benefiting from the specific binding between HA and CD44 receptors. Biodistribution results further demonstrated the increased accumulation of HA-CUR in kidneys with 13.9-fold higher than that of free CUR. Pharmacodynamic studies indicated HA-CUR effectively ameliorated AKI, and the exact mechanism was that HA-CUR protected renal tubule epithelial cells from oxidative stress damage via inhibiting PtdIns3K-AKT-mTOR signaling pathway. Taken together, this study provides a new therapeutic strategy for the treatment of AKI based on the pathogenesis of the disease.